Breast Reconstruction in Obese Patients: The Fat Grafted Latissimus versus Abdominal Free Tissue Transfer. Issue 3 (17th March 2020) - Novak, Matthew D.; Blough, Jordan T.; Abraham, Jasson T.; Shin, Hope D.; Yasuda, Tai; Ayala, Donna; Altman, Andrew M.; Saint-Cyr, Michel
Abstract : Background: Immediate fat grafting to the pedicled myocutaneous latissimus dorsi (LD) flap has recently gained in popularity as a means to supplement volume for breast reconstruction. The aim of this study is to compare complication rates of the immediately fat-grafted LD to free tissue transfer in the obese population. Methods: In this retrospective cohort, 82 patients (149 breasts) from 2015 to 2019 were included. Patients underwent either unilateral or bilateral breast reconstruction with either LD with immediate fat grafting or abdominal-based free tissue transfer. Included patients had a body mass index ≥ 30 kg/m 2 at the time of surgery. Complication data were recorded as minor, major, and medical complications. Procedure characteristics and postoperative data were also studied. Results: Minor complication rates between the LD with immediate fat grafting and free tissue transfer cases were similar (26.9% versus 26%, respectively). The free tissue transfer group had a significantly higher rate of major complications (20.3% versus 3.8%; P = 0.048) and medical complications (10.6% versus zero). Finally, the LD with immediate fat grafting group had significantly shorter operating room times, hospital length of stay, and fewer donor-site revisions. Conclusions: LD with immediate fat grafting offers the benefit of a totally autologous reconstruction without the risks of abdominal-based microvascular free tissue transfer or an implant. Favorable complication rates, shorter operative times, and shorter hospital length of stay make this reconstructive option a safe alternative to free tissue transfer in the obese population.